Narrativas de professoras de educação infantil : revisitando suas trajetórias pessoais e profissionais em momentos de formação continuada - Rangel, Alexandra Maria Vieira (2016)
This dissertation proposed research the continuing education processes developed in a Municipal Kindergarten Centre (CMEI, its acronym in Portuguese in the city of Serra) and it had as objective to investigate the possibilities of the narratives of early childhood education teachers enhance educational processes within a Municipal Center for Child Education. As complementary objectives were defined: a. Analyzing municipal documents and documents from the educational institution itself in order to understand how they have configured the formations offered to the teachers of Early Childhood Education; b. Analyze the tensions between the official documents about continuing education in the municipality and the narratives of teachers of early childhood education; c. Identify in the narratives of the teachers their perception on continuing education; d. Analyze clues of professional development of the teachers during the training process. The theoretical assumptions that supported this research work were as follows: Specifically in the field of teacher training, we established dialogues with Nóvoa and Imbernon. In relation to narrative perspective on processes of research-training we used contributions from Souza, and for the debates in the field of early childhood education we use some of Kramer's contributions. The methodological assumptions used were the perspective of narrative research, from Souza, combined with some of the principles of participatory research, from Thiollent. The instruments for data collection were: narrative interviews, participant observation and recording in the field diary. The results indicate that the narratives of the teachers show an extremely important tool to enhance the continuing education processes within the Municipal Center for Early Childhood Education. In relation to the tensions inherent in the normative documents the analysis indicates the need for continued training policy that expresses the needs of continuing education in a better way.